Young guns [videorecording (DVD)] - Cain, Christopher, 1943-; Estevez, Emilio, 1962-; Sutherland, Kiefer, 1966-; Phillips, Lou Diamond, 1962- (Artisan Home Entertainment, 2003)
A portrait of Billy the Kid and his gang as they move from prairie trash to demi-gods.